Physico-chemical Studies and Trace Elemental Analyses of Some Spring and Well Water in and Around Some Selected Districts of Nagaland, India - TIAKABA JAMIR, T.; BHUBON SINGH, R.K. (Asian Journal of Chemistry, 2010)
Physico-chemical parameters such as temperature, pH, conductivity, TDS, total hardness, dissolved oxygen, BOD and COD were determined while the level of essential trace elements namely iron, copper, zinc, nickel, manganese and non-essential trace elements namely lead, cadmium, silver and arsenic have been determined from three different districts of Nagaland, India. It was found that the samples collected have physicochemical parameters in the range of permissible limits prescribed by ISI and WHO. The concentrations of the essential and non-essential trace elements were evaluated by using atomic absorption spectroscopy. Comparing these results with the WHO guidelines for the domestic water revealed that the concentration of lead, iron and manganese in many samples under investigation were within the elevated values. These finding shows that waste materials have been passed into the rivers ponds by human and/or industrial activities.